Quadruple‐Junction Thin‐Film Silicon Solar Cells Using Four Different Absorber Materials. Issue 3 (31st March 2017) - Si, Fai Tong; Isabella, Olindo; Tan, Hairen; Zeman, Miro
Abstract : We fabricated and studied quadruple‐junction wide‐gap a‐Si:H/narrow‐gap a‐Si:H/a‐SiGe x :H/nc‐Si:H thin‐film silicon solar cells. It is among the first attempts in thin‐film photovoltaics to make a two‐terminal solar cell with four different absorber materials. Several tunnel recombination junctions were tested, and the n‐SiO x :H/p‐SiO x :H structure was proven to be a generic solution for the three pairs of neighboring subcells. The proposed combination of absorbers led to a more reasonable spectral utilization than the counterpart containing two nc‐Si:H subcells. Besides, the use of high‐mobility transparent conductive oxide and modulated surface texture significantly enhances the total light absorption in the absorber layers. This work paved the way toward high‐efficiency quadruple‐junction cells, and a practical estimation of the achievable efficiency was given. Abstract : Quadruple‐junction thin‐film silicon solar cells are made using four absorber materials with different bandgaps. The proposed device shows improved spectral utilization with reduced spectral overlap. Various tunnel recombination junctions are studied to achieve optimal electrical interconnections. The modulated surface textured front electrode is used to enhance broadband light absorption. The practical potential of such a device is discussed.